Makna Mengampuni dalam Matius 18:21–22: Kajian Biblika dan Implikasinya bagi Umat Kristen Masa Kini - Alvin Budiman Kristian; Resa Junias (KHARISMATA: Jurnal Teologi Pantekosta, 2026)
Forgiveness is a central teaching of Christianity, but its practice often faces challenges due to interpersonal conflict, retaliation, and the phenomenon of cancel culture. Therefore, an examination of Matthew 18:21–22 is crucial for understanding the meaning of forgiveness in Jesus' teachings and its relevance for the church today. This research uses qualitative methods with a biblical approach through historical-contextual and linguistic analysis of the text of Matthew 18:21–22. The results show that forgiveness is not merely a moral requirement, but a relational principle aimed at restoring community and building reconciliation. The phrase "seventy times seven" emphasizes that forgiveness must be a limitless attitude. This research contributes to demonstrating that forgiveness has spiritual and social dimensions that are relevant for the church in addressing conflict and polarization in modern society.   Pengampunan merupakan ajaran utama dalam kekristenan, tetapi praktiknya sering menghadapi tantangan akibat konflik interpersonal, budaya pembalasan, dan fenomena cancel culture. Karena itu, kajian terhadap Matius 18:21–22 penting untuk memahami makna pengampunan dalam ajaran Yesus dan relevansinya bagi gereja masa kini. Penelitian ini menggunakan metode kualitatif dengan pendekatan kajian biblika melalui analisis historis-kontekstual dan linguistik terhadap teks Matius 18:21–22. Hasil penelitian menunjukkan bahwa pengampunan bukan sekadar tuntutan moral, melainkan prinsip relasional yang bertujuan memulihkan komunitas dan membangun rekonsiliasi. Frasa “tujuh puluh kali tujuh kali” menegaskan bahwa pengampunan harus menjadi sikap hidup tanpa batas. Penelitian ini berkontribusi dalam menunjukkan bahwa pengampunan memiliki dimensi spiritual dan sosial yang relevan bagi gereja dalam menghadapi konflik dan polarisasi di tengah masyarakat modern.